Coping strategies used by nurses during the COVID-19 pandemic: A narrative literature review - Leepile A. Sehularo; Boitumelo J. Molato; Isaac O. Mokgaola; Gopolang Gause (AOSIS, 2021)
Background: During the coronavirus disease 2019 (COVID-19) pandemic, it is understandable that nurses are working under stressful conditions. A successful use of effective coping strategies during the COVID-19 pandemic will help nurses to manage stressful conditions. Aim: The objective of this narrative literature review was to explore and describe the coping strategies used by nurses during the COVID-19 pandemic. Setting: This study was conducted from all available literature related to the coping strategies used by nurses during the COVID-19 pandemic globally. Methods: A narrative literature review was conducted to answer researchers' concern of coping strategies used by nurses during COVID-19. The purposive sampling technique was used to select three online databases that were used to search for the relevant literature, namely Google Scholar, Science Direct and African Journals (formerly SAePublications). Search terms used to conduct this study include coping, coping strategies, nurses, nursing and COVID-19 pandemic. This study included English studies focusing on coping strategies used by nurses during COVID-19 published between 2019 and 2021. The study excluded newspaper articles, conference reports and other databases not mentioned in this study. Results: The findings identified the following strategies: use of COVID-19 protective measures, avoidance strategy, social support, faith-based practices, psychological support and management support are used by nurses as coping strategies during the COVID-19 pandemic. Conclusion: The use of the identified coping strategies by nurses may reduce stress and burnout during the COVID-19 pandemic. Recommendations were made for future research, nursing education and practice. Contribution: This is the first narrative literature review focusing on the coping strategies used by nurses during the COVID-19 pandemic. The findings of this narrative literature review provide insight that may be used by nurses of all categories to cope during the COVID-19 pandemic.